Resolution of Gallstone Ileus with Spontaneous Evacuation of Gallstone: A Case Report - Tandon, Anupama (Springer India, 2013)
Gallstone ileus is an infrequent complication of cholelithiasis. The formation of a fistula between the gallbladder and duodenum may allow a gallstone to enter the gastrointestinal (GI) tract. Gallstone ileus generally occurs in the elderly patients and is associated with significant mortality. Spontaneous resolution of gallstone ileus after passage of gallstone per rectally, though rare, has been reported Farooq et al. (Emerg Radiol 4(6):421–423, 2007). We describe a 60-year-old woman who presented with a 3-day history of vomiting, pain, distension and constipation .Radiological investigations revealed dilatation of small bowel loops with multiple air fluid levels with a large lamellated radio-opaque density measuring 4.4 cm × 4 cm seen in the right iliac fossa. A possibility of gallstone ileus was kept. Because of co-morbid conditions (post-myocardial infarct with cardiac failure), surgery could not be done and patient was kept on conservative management. Three days later patient had sudden relief of her symptoms after passing a large calculus per rectally suggesting a spontaneous evacuation of gallstone. This case highlights the possibility of spontaneous resolution of gallstone ileus after the passage of gallstone. It has been reported in stones less than 2.5 cm. However, to the best of our knowledge, this is the first time in which a large stone measuring 4 cm × 3.8 cm passed spontaneously.